Perceptions of nurse managers and staff nurses regarding Technological Competency as Caring in Nursing theory in general hospitals in Japan - Nakano, Youko; Yokotani, Tomoya; Betriana, Feni; Kawai, Chihiro; Ito, Hirokazu; Yasuhara, Yuko; Tanioka, Tetsuya; Locsin, Rozzano; Miyagawa, Misao (Belitung Raya Foundation, Indonesia, 2021)
Background: Nurses as primary healthcare providers demonstrate quality nursing care through competencies with healthcare technologies, while nurse managers assume the primacy of managing quality healthcare in their respective care settings. However, little is known about perceptions of the influence of care technologies on their nursing practice. Objective: This study aimed to determine managers’ and staff nurses’ perceptions regarding the Technological Competency as Caring in Nursing (TCCN) theory in general hospitals in Japan. Methods: This study employed a cross-sectional survey design, with 421 participants selected using a stratified sampling method. Technological Competency as Caring in Nursing Instrument–Revised (TCCNI-R) was used for online data collection using Survey Monkey©. Data were analyzed using Welch’s t-test and ANOVA. Results: Nurses with years of experience within the range of 20 to less than 30 years showed the highest TCCNI-R scores among the two groups. Nurses who had received education on caring in nursing showed significant differences for Factor 2 (Technological Competency as Caring), that of expressing Technological Competency as Caring. Three other factors showed no significant difference, namely in Factor 1 (Nursing Expression as Caring), Factor 3 (Technology and Caring), and Factor 4 (Technological Knowing). However, the average scores of these factors were high, which reflect high professional ethics and occupational discipline and increased awareness of caring in nursing. It was also found that the nurse managers were more aware of the TCCN than were the staff nurses. The nurse managers were also more aware of providing care using technology, recognizing the need-to-know patient needs through technology and providing care to the ever-changing patient’s condition. Conclusion: The study discovered that continuing education is needed regarding the practice of nursing based on theory, enabling appropriate and accurate understanding of practicing knowing persons as caring in nursing.